Status Aspirations, Wealth Inequality, and Economic Growth - Oded Stark (University of Bonn, Center for Development Research (ZEF), 2005)
This paper argues that an increase in the inequality of wealth prompts a stronger quest for status that in turn fosters the accumulation of wealth. It proposes a measure for an individual's want of social status. For a given level of a population?s wealth, the corresponding aggregate measure of want of social status is shown to be positively related to the Gini coefficient of wealth inequality. Hence the Gini coefficient and growth are positively correlated, holding the population?s wealth constant. – – Dieser Diskussionsbeitrag zeigt, dass eine Zunahme des Wohlstandsgefälles ein stärkeres Streben nach Status nach sich zieht, was wiederum die Anhäufung von Wohlstand fördert. Es schlägt ein Maß für das individuelle Streben nach sozialem Status vor. Für ein gegebenes Niveau des Wohlstandes einer Bevölkerung steht das entsprechende aggregierte Maß des Strebens nach sozialem Status in positiver Beziehung zum Gini-Koeffizienten der Ungleichheit des Wohlstandes. Somit korrelieren der Gini-Koeffizient und das Wachstum positiv miteinander und halten dadurch den Wohlstand einer Bevölkerung konstant.
Keywords: O40; D63; A14; D31; A13; 330; Quest for status; Distribution of wealth; Economic growth; Vermögensverteilung; Einkommensverteilung; Sozialer Status; Wirtschaftswachstum; Theorie